2011
DOI: 10.1038/ja.2011.110
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel deoxyribofuranosyl indole antimicrobial agents

Abstract: Three novel deoxyribofuranosyl indole derivatives, FG050227 (1), FG050223 (2) and FG050204 (3), were identified as antimicrobial agents effective against Gram-positive bacterial strains and some fungi. The MIC values of (1), (2) and (3) against methicillin-resistant Staphylococcus aureus were 3.0, 6.0 and 13 lg ml À1 , respectively. Compounds 1 and 3 had bactericidal activity against exponentially growing S. aureus and inhibited biosynthesis of peptidoglycan, protein, RNA and DNA. Compound 2 was bacteriostatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Purification based on in vitro activity alone may miss to identify therapeutically effective compounds. Furthermore, our previous experience of selecting the hits from a chemical library using minimum inhibitory concentrations (MIC) as an indicator showed that these compounds had no therapeutic activity (Paudel et al, 2012, 2013). Therefore, we chose to evaluate the therapeutic activity using the silkworm infection model to purify therapeutically effective compounds.…”
Section: Advantage Of Screening Novel Antibiotics Using the Silkworm mentioning
confidence: 99%
“…Purification based on in vitro activity alone may miss to identify therapeutically effective compounds. Furthermore, our previous experience of selecting the hits from a chemical library using minimum inhibitory concentrations (MIC) as an indicator showed that these compounds had no therapeutic activity (Paudel et al, 2012, 2013). Therefore, we chose to evaluate the therapeutic activity using the silkworm infection model to purify therapeutically effective compounds.…”
Section: Advantage Of Screening Novel Antibiotics Using the Silkworm mentioning
confidence: 99%
“…Moreover, some of these resistant strains, community-associated methicillin-resistant S. aureus (CA-MRSA), have acquired higher virulence potentials than those of hospital-associated methicillin-resistant S. aureus (HA-MRSA) (4,5). Our research group has investigated various aspects of the virulence mechanisms of S. aureus, e.g., identification and characterization of novel virulence genes (6); investigation of the involvement of the staphylococcal cassette chromosome mec element (SCCmec), a mobile genetic element that provides methicillin resistance, in pathogenesis (7,8); analysis of activation mechanisms of innate immunity by use of insects as animal models (9-13); and searching for new antibiotics with novel chemical structures (14,15). These studies have provided some insights into sepsis and have contributed to the establishment of some drug therapies.…”
mentioning
confidence: 99%
“…The sources of the strains are indicated by asterisks .* Hamamoto et al, 2015 ,** Suzuki et al, 2011 ,*** Paudel et al, 2012 .…”
Section: Resultsmentioning
confidence: 99%
“…The amount of incorporated radiolabeled precursors was measured as previously described (Maki et al, 2001; Paudel et al, 2012, 2013). S. aureus RN4220 was grown to exponential phase and used for the assay in the presence of 25 μci [ 3 H] N -acetyl-glucosamine (American Radiolabeled Chemicals, St. Louis, MO, USA) or 2 μci/mL of either [ 3 H] uridine (Moravek Biochemical, Brea, CA, USA), [ 3 H] thymidine (Moravek Biochemical), or [ 35 S] methionine (Institute of Isotopes, Budapest, Hungary).…”
Section: Methodsmentioning
confidence: 99%